Effects of Motor Skill Intervention on Gross Motor Development, Creative Thinking and Academic Performance in Preschool Children - Jiménez Díaz, Judith (2009)
The purpose of this study was to investigate how students (mean= 6.08±0.5 years) benefit from a physical education program in motor performance, creative thinking and academic achievement. Students (n = 39) were randomly assigned to comparison group (6 boys and 7 girls) who received the regular preschool program (which includes 1 session of 30 minutes per week); intervention group 1 (6 boys and 7 girls) who received the regular preschool program plus 1 session of 30 minutes per week of the intervention program; or intervention group 2 (6 boys and 7 girls), who received the regular preschool program plus 1 session of 60 minutes per week of the intervention program; during 8 weeks. All participants performed the Test of Gross Motor Development (TGMD-2) and the Torrance Test of Creative Thinking (TTCT) before and after the study. The academic achievement score was given by the school. The ANOVA (Group x Gender x Time pre and post) analysis revealed a significant triple interaction in the object control. Significant double interactions in the locomotor subscale and in the gross motor quotient were also found. After the post-hoc analysis, the results suggest that the physical education program benefits the gross motor performance and did not have an effect on the creative thinking or on the academic achievement.